Depression and anxiety disorders among schoolgoing adolescents in an urban area of South India - K Jayashree; P Prasanna Mithra; M K C. Nair; Bhaskaran Unnikrishnan; Keshava Pai (Wolters Kluwer Medknow Publications, 2018)
Context: Adolescence is a period of turmoil, leading to several mental health challenges including anxiety and/or depression. Aims: To study the prevalence of depression and anxiety among higher school going adolescents and their sociodemographic correlates. Settings and Design: This cross-sectional study included 201 schoolgoing adolescents. Subjects and Methods: Depression and anxiety were measured using Beck Depression Inventory and Screen for Child Anxiety Related Disorders. Statistical Analysis Used: Chi-square test and binary logistic Regression with Hosmer-Lemeshow goodness-of-fit model. Results: Overall, 82 (40.8%) showed depression (from mild mood disturbance to severe and extreme depression). Among females, it was 49.3% (vs. 35.9% among males, odds ratio [OR] 2.00; 95% confidence interval [CI]: 1.02-03.97, P = 0.046). Overall, 110 (54.7%) participants had one or the other type of anxiety. Depression among the participants having one or other type of anxiety was 60% (vs. 17.6% without anxiety, OR 7.34; 95% CI: 3.68-14.64, P < 0.0001). Conclusions: Depression and anxiety were high among the study participants. Co-existing anxiety and female gender are significantly associated with depression among them. Increasing age, socioeconomic factors, and parental education are other factors influencing depression and anxiety but were statistically not significant.